The Acceptability and Feasibility of Implementing an Online Educational Intervention With Nurses in a Provincial Prison Context. Issue 3 (July 2019) - Almost, Joan; Gifford, Wendy A.; Doran, Diane; Ogilvie, Linda; Miller, Crystal; Rose, Donald N.; Squires, Mae; Carryer, Jennifer; McShane, Julie; Miller, Kim
ABSTRACT: Background: Correctional nursing requires a strong knowledge base with access to continuing education (CE) to maintain and enhance competencies. Nurses working in provincial prisons have reported many challenges in accessing CE, with online learning being identified as a potential solution. Limited research was found, however, which examined the correctional context in the development and delivery of online learning for nurses. The purpose of this study was to develop an online educational intervention tailored to correctional nurses and determine the feasibility and acceptability of implementing the intervention in a provincial prison context. Methods: A sequential mixed methods study was conducted. Participants included nurses from three correctional settings in the province of Ontario, Canada. Semistructured interviews examined contextual factors and educational needs. Delphi surveys determined the educational topic. Preintervention and postintervention questionnaires examined the context, educational content, and intervention's acceptability and feasibility. Results: The online intervention focused on mental health and addictions with two 30-minute webinars delivered back-to-back over 15 weeks. Respondents expressed satisfaction with the convenience of online learning at work using short webinars, as well as the topics, relevance of information, and teaching materials, but dissatisfaction with presentation style. The feasibility of the intervention was limited by access to technology, time to attend, education space, and comfort with technology. Discussion: The findings from this study provide insight to guide the future development of online CE for correctional nurses. If changes are made within correctional facilities in collaboration with nurses and managers, online learning holds the potential to facilitate access to ongoing professional development.